ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI SAWAH DI DESA SALEMBA KECAMATAN UJUNG LOE KABUPATEN BULUKUMBA - Hamjah, Muhammad Reza; Lamusa, Arifuddin; Muis, Abdul (AGROTEKBIS, 2018)
The purpose of this study wastodetermine the income and the feasibility of wetland rice farming in Salemba village Ujung Loe district Bulukumba regency. A total number of 35 farmers were purposively selected as respondents. Data was analyzed using revenue and feasibility analyses. The results showed that the wetland rice income was IDR7,113,014.19/ha. The wetland rice farming is feasible to be developed as indicated by the R/C value of 2.36 suggesting that for every IDR 100 spent will generate revenue of IDR 236.Â Key words: Income, Feasibility, and Wetland rice farming.